Implications of the new AUA guidelines on prostate cancer detection in the US - Cooperberg, Matthew R. (Curr Urol Rep, 2014)
In 2012 the US Preventive Services Task Force (USPSTF) issued a blanket “D” recommendation against all prostate specific antigen (PSA)-based early detection efforts for prostate cancer, reflecting critical misinterpretations of the major evidence regarding benefits and harms of such testing. Against the backdrop of the ensuing controversy, the American Urological Association (AUA) published a new, methodologically rigorous guideline in 2013. This guideline recommended that men aged 55-69 be offered biannual screening in the setting of shared decision-making, that men under 40 or over 69 should not be screened routinely, and that evidence was insufficient to recommend screening for men 40-54. The AUA guideline has been criticized regarding the age-based recommendations, but reflects a far better and more balanced presentation of the available evidence than the USPSTF statement. However, because the USPSTF is far more influential than the AUA among primary care providers, the ultimate impact of the new AUA guideline on practice patterns may be limited. Optimizing early detection practices should involve consensus-building incorporating both primary care and specialist input, with the goals of minimizing over-treatment of low-risk disease while continuing to reduce prostate cancer mortality rates through early detection and aggressive management of high-risk disease.